Teachers' Perceptions of Research Culturalization in Elementary Schools - Novi Sylvia; Deni Hadiana; Yuyun Libriyanti; AM Saifullah Aldeia; Evi Sopandi (Jurnal Ilmiah Sekolah Dasar, 2024)
Research culture is fundamental in developing educational practices in schools that are based on proven knowledge and data. Culturalization at the elementary school level is the foundation for developing a research culture at the higher school level. Teachers' perceptions can provide benchmarks for research culturalization practices in schools as the ultimate base of a research-based mindset. This research aims to analyze research culturalization as perceived by teachers in elementary schools. The method used is descriptive qualitative with a questionnaire that measures teachers' perception towards fifteen aspects of research Culturalization. Data analysis from 379 teachers of local elementary schools shows that: (1) the percentage of teachers' perceptions regarding knowledge of research culture is 57% just starting; (2) the percentage of teacher perceptions related to understanding is 55% just starting; and (3) the percentage of teacher perceptions related to practice is 69% just starting. These results indicate that the culturalization of research based on teacher perceptions is at a will-do level regarding knowledge, understanding, and practice indicators. Teachers' perceptions are alike in knowledge and understanding and higher in practice. These findings conclude an awareness and enthusiasm of research culturalization significance that should be supported by all stakeholders involved, such as the government, teachers, leaders, and other educators involved in the schools. These findings also provide challenges for policies and practices that align with research culturalization indicators in elementary schools.